2022
DOI: 10.3390/s22134674
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Assisted Handheld Confocal Raman Micro-Spectroscopy for Identification of Clinically Relevant Atopic Eczema Biomarkers

Abstract: Atopic dermatitis (AD) is a common chronic inflammatory skin dermatosis condition due to skin barrier dysfunction that causes itchy, red, swollen, and cracked skin. Currently, AD severity clinical scores are subjected to intra- and inter-observer differences. There is a need for an objective scoring method that is sensitive to skin barrier differences. The aim of this study was to evaluate the relevant skin chemical biomarkers in AD patients. We used confocal Raman micro-spectroscopy and advanced machine learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This review covers methods demonstrated in the literature as viable skin hydration sensors and in some cases that have been used on skins with eczema. Raman spectroscopy focuses on the scattering of light, and it measures the intensity of scattering events occurring at specific wavelengths, thereby estimating the concentration of molecules with known scattering effects at these frequencies [96]. Near-Infrared Spectroscopy (NIRS) monitors the absorption intensity from the reflectance spectrum of an exposed tissue or material within the near-infrared band (wavelengths of 0.8 to 2.5 mm).…”
Section: Optical Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations
“…This review covers methods demonstrated in the literature as viable skin hydration sensors and in some cases that have been used on skins with eczema. Raman spectroscopy focuses on the scattering of light, and it measures the intensity of scattering events occurring at specific wavelengths, thereby estimating the concentration of molecules with known scattering effects at these frequencies [96]. Near-Infrared Spectroscopy (NIRS) monitors the absorption intensity from the reflectance spectrum of an exposed tissue or material within the near-infrared band (wavelengths of 0.8 to 2.5 mm).…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…Confocal Raman Micro-Spectroscopy (CRM) is a type of Raman spectroscopy widely used to perform non-invasive in vivo measurements on the SC and EP layers of the skin, as it can determine the biomolecular composition at depths up to several hundred micrometers [96]. The method uses the variance in scattered protons depending on the chemical content to provide a unique signature Raman spectrum for each material measured.…”
Section: Raman Spectroscopy Measurements On Skinmentioning
confidence: 99%
See 2 more Smart Citations
“…CRM has been widely used in the past to examine HS [51][52][53][54], the effects of ageing [55], and psoriatic skin [56][57][58]. So far, CRM has already been applied in AD to study the impact of filaggrin mutations [59][60][61], to compare sensitive skin with atopic and non-sensitive skin [62], to compare HS with lesional atopic and psoriatic skin [63], and to create an objective classification score for AD [64]. Janssens et al have focussed on the lipid analysis of atopic skin [65], and Verzeaux et al studied several molecular SBF-related parameters comparing LAS and HS up to a depth of 12.5 µm in the SC [66].…”
Section: Introductionmentioning
confidence: 99%